2004
DOI: 10.1007/s11137-005-0014-9
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation of microamounts of Cs with ferrocyanides of various metals

Abstract: Coprecipitation of microamounts of Cs with ferrocyanides of various metals, exhibiting a high sorption activity with respect to Cs ions, was studied. The distribution coefficients of 117 Cs were determined in coprecipitation with the ferrocyanides in 0.1 M NaNO 3 . The precipitated ferrocyanide was separated from solution by filtration through a Trumem metal!ceramic membrane. Cesium is recovered most efficiently with ferrocyanides of bivalent transition metals (Ni, Co, Cu, Fe, Cd).Utilization of liquid radioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Additionally, metal hexacyanoferrates are known to interchange Cs þ from aqueous solutions. Cs þ can be recovered from radioactive wastes by co-precipitation with those complexes [9,10]; they can adsorb almost 100% of the Cs þ from simulated radioactive wastes [10]. The above information suggests that Cs þ could be preconcentrated on a NiHCFe-Al 2 O 3 modified electrode.…”
mentioning
confidence: 91%
“…Additionally, metal hexacyanoferrates are known to interchange Cs þ from aqueous solutions. Cs þ can be recovered from radioactive wastes by co-precipitation with those complexes [9,10]; they can adsorb almost 100% of the Cs þ from simulated radioactive wastes [10]. The above information suggests that Cs þ could be preconcentrated on a NiHCFe-Al 2 O 3 modified electrode.…”
mentioning
confidence: 91%
“…During the modification processes the fixing of ion exchange or complexing groups on the surface of the LC-matrix can take place. One way to obtain selective composite sorbents toward cesium ions is the impregnation of plant materials with the solutions of ferrocyanides of d-metals ([FC]M, where М -Fe 3+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ ) [5][6] that characterized by high selectivity with respect to cesium [7] that considered as the most hazardous among all radionuclides due to relatively long half-life, high toxicity and migration properties. Such composite materials based on plant raw material can also be used as enterosorbents to prevent pollutant accumulation in human and animal body.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that LDH-Mg-Al-Anion (Anion = CO 3 2-, NO 3 -) solid phases did not take up 131 I in the form of 131 Iand 131 IО 3 from aqueous solutions, whereas the efficiency of the 131 Iand 131 IО 3 removal from aqueous solution with SDO-Mg-Al exceeded 99%. Synthetic analogs of hydrotalcite of the composition LDH-Mg-Al-Nd-CO 3 and LDH-Mg-Nd-CO 3 allowed 90 Sr 2+ and 90 Y 3+ to be removed from aqueous solutions with more than 99% efficiency [2].…”
mentioning
confidence: 99%
“…The compounds LDH-Mg-M 3+ -CO 3 (M 3+ = Al, Nd) remove 233,238 U(VI) from aqueous solutions of complex chemical composition with more than 99% efficiency [1]. 60 Со is efficiently sorbed from 10 -3 -10 -5 M aqueous Co(NO 3 ) 2 solutions onto LDH-Mg-Al and LDH-Mg-Nd with CO 3 2ions in the interlayer space. At the contact time of the solid and liquid phases (τ) of 15 min and V/m = 50 mL g -1 , K d exceeds 2 × 10 4 mL g -1 for LDH-Mg-Nd and does not exceed DOI: 10.1134/S1066362215010105 EXPERIMENTAL 5 × 10 3 mL g -1 for LDH-Mg-Al [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation